European Tourist Perspective on Destination Satisfaction in Jordan’s industries - Araslı, Hüseyin; Baradarani, Sarvnaz (Elsevier, 2014)
Extant tourism literature reveals that the travelers’ satisfaction from a tourist destination is a significant determinant of their post-holiday behaviors. The aim of this study was to investigate the effects of these variables on European tourist perspective and to examine the relationship between destination satisfaction and positive word of mouth of the tourists visiting Amman, Jordan. European travelers participated by filling out a self administered questionnaire. A sample of 208 tourists was collected through convenience sampling, at 3, 4 and 5 star hotels in Amman. The lodging and transportation dimensions were found to have an insignificant effect on destination satisfaction. Food and local cuisine, shopping and tourist attractions and environment and safety were found to have a significant effect on destination satisfaction. In spite of that lodging and restaurant facilities, transportation facilities and infrastructure were found to have insignificant effect on destination satisfaction.
The file in this item is the publisher version (published version) of the article.
Keywords: Destination satisfaction; European tourists; tourism; Jordan; positive word of mouth